Effect of laser power on selective laser melting of TiC strengthened 316L stainless - Tungul, Zirrom Umlas (Nanyang Technological University, 2021)
The addition of titanium carbide (TiC) particles in austenitic 316L stainless steel (SS) overcomes the material’s inherent disadvantage of having a low-yield strength in its annealed state. In contrast to conventional manufacturing techniques, selective laser melting (SLM) provides a more efficient method in the fabrication of homogenous TiC strengthened 316L SS. This paper studies the effect of laser power in fabricating a near fully dense 3 wt% TiC particle-reinforced 316L SS (316L-3TiC) parts using Selective Laser Melting (SLM). Micron-sized TiC particles, sizes ranging from 0.5-21 μm, were dispersed uniformly in the 316L powder using low-energy ball milling prior to fabrication. Test samples were then SLM fabricated using varying laser power, forming ex-situ 316L- 3TiC metal matrix composites (MMCs). Their microstructures were studied under scanning electron microscope (SEM) and optical microscope. The samples were also subjected to Vickers hardness test, relative density test and tensile test. The effect of the varying laser power on the mechanical property and microstructure of the samples were studied and were used to conclude the effect of laser power in SLM fabrication of 316L-3TiC parts. In this study, it was found that laser power of 225 W or laser energy density of 133.9 J/mm3 was the optimum laser parameter in SLM fabrication of 316L-3TiC.